A Man “Resembling Sancho Panza”: Viktor Petrov's Self-Presentation in Letters to Sofiia Zerova - Valentyna Borbuniuk (Вісник Харківського національного університету імені В. Н. Каразіна. Серія Філологія. Vìsnik Harkìvsʹkogo nacìonalʹnogo unìversitetu ìmenì V.N. Karazìna. Serìâ Fìlologìâ.)
The original figure of V. Petrov (1894–1969) is still in the halo of mystery and unsolved. This is due to his remarkable personality and the scarcity of self-representative texts, including letters, available in the public domain.